Engaging Australian men in disease prevention - priorities and opportunities from a national survey - Ben J Smith; Timothy J Moss; Bernie Marshall; Nicole Halim; Robert Palmer; Simon von Saldern (Sax Institute, 2024)
Objective and importance of the study: In Australia, preventable causes of morbidity and mortality are common among men. The National Men's Health Strategy 2021-2030 highlights the need to successfully engage men in disease prevention; hence, we aimed to examine the prevention priorities, attitudes and information sources reported by Australian men. Study type: Population survey. Methods: Men aged 18 years and over were recruited from the nationally representative Life in Australia panel. Participants completed an online survey that measured the prevention issues of greatest concern, attitudes to prevention behaviours and services, and the health information sources considered most useful. Results: Among 1282 respondents, mental health issues, followed by those pertaining to chronic disease and relationships, were rated of highest concern. Weight management, physical activity, and fruit and vegetable consumption were most often considered as important for personal health. Being 65 years and older and having adequate health literacy were strongly associated with positive attitudes towards prevention practices. More than three-quarters of men rated their doctor as the most useful information source, followed by health websites, internet searching, and their partner. Conclusions: Psychological and social issues are of high concern to men, and their attitudes toward preventive behaviours and services often do not align with public health recommendations. Understanding the topics of greatest concern to men and their preferred sources of information can inform communication and engagement strategies to improve health-related practices among men.